Smart homes, smarter living: home automation with IoT - Lu Fan (Big Data and Computing Visions)
This paper will explain that the growing global population and increasing energy utilization have underscored the urgent need to conserve energy through every available means. One significant factor contributing to energy waste is the lack of access to and control over applications from remote locations. To mitigate this issue, users can utilize web or Android applications to send instructions to these systems. Communication protocols such as Wi-Fi, GSM, bluetooth, and ZigBee can be leveraged to establish connectivity between the design and user devices. Existing systems feature diverse monitoring devices and structural components to facilitate efficient energy management. Numerous examples of such applications have already been implemented in various settings. By harnessing these technologies, users can remotely control and monitor their energy consumption, reducing energy waste and promoting environmental sustainability. Continued research and development of energy-saving solutions will be critical in mitigating the negative impact of rising energy demand.